Ð’Ð»Ð¸ÑÐ½Ð¸Ðµ ÐºÑ€Ð¸Ð¾ÐºÐ¾Ð½ÑÐµÑ€Ð²Ð¸Ñ€Ð¾Ð²Ð°Ð½Ð¸Ñ Ñ Ð”ÐœÐ¡Ðž Ð½Ð° ÑÐ¾Ñ…Ñ€Ð°Ð½Ð½Ð¾ÑÑ‚ÑŒ Ð¸ Ð¾ÑÐ¼Ð¾Ñ‚Ð¸Ñ‡ÐµÑÐºÑƒÑŽ Ñ…Ñ€ÑƒÐ¿ÐºÐ¾ÑÑ‚ÑŒ ÑÑ€Ð¸Ñ‚Ñ€Ð¾Ñ†Ð¸Ñ‚Ð¾Ð² Ñ€Ð°Ð·Ð»Ð¸Ñ‡Ð½Ñ‹Ñ… Ð²Ð¸Ð´Ð¾Ð² Ð¼Ð»ÐµÐºÐ¾Ð¿Ð¸Ñ‚Ð°ÑŽÑ‰Ð¸Ñ… - Ulizko, P. Yu.; Zhegunov, G. F.; Denisova, O. N. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2011)
In the research there was studied the hemolysis level of bovine, equine, and rabbit erythrocytes in different hypotonic media after incubation and freeze-thawing with 10% dimethyl sulfoxide (DMSO) solution. It was shown, that intact erythrocytes of all the examined animals demonstrated the similar osmotic stability in hypotonic conditions, and DMSO in the stated concentration does not significantly affect this parameter and red blood cell integrity. The use of 10% DMSO during freeze-thawing without washing-out the cryoprotectant allows to preserve up to 80% erythrocytes, however, the process of cryoprotectant removal reduces this index.